Enhancing Clinical Research Professionals' Training and Qualifications (ECRPTQ): Recommendations for Good Clinical Practice (GCP) training for investigators and study coordinators. Issue 1 (13th January 2017) - Shanley, Thomas P.; Calvin-Naylor, Nancy A.; Divecha, Ruthvick; Wartak, Michelle M.; Blackwell, Karen; Davis, Jonathan M.; Ellerbeck, Edward F.; Kieburtz, Karl; Koziel, Margaret J.; Luzuriaga, Katherine; Maddox, Jennifer; Needler, Nancy A.; et al.
Abstract : Introduction: The translation of discoveries to drugs, devices, and behavioral interventions requires well-prepared study teams. Execution of clinical trials remains suboptimal due to varied quality in design, execution, analysis, and reporting. A critical impediment is inconsistent, or even absent, competency-based training for clinical trial personnel. Methods: In 2014, the National Center for Advancing Translational Science (NCATS) funded the project, Enhancing Clinical Research Professionals' Training and Qualifications (ECRPTQ), aimed at addressing this deficit. The goal was to ensure all personnel are competent to execute clinical trials. A phased structure was utilized. Results: This paper focuses on training recommendations in Good Clinical Practice (GCP). Leveraging input from all Clinical and Translational Science Award hubs, the following was recommended to NCATS: all investigators and study coordinators executing a clinical trial should understand GCP principles and undergo training every 3 years, with the training method meeting the minimum criteria identified by the International Conference on Harmonisation GCP. Conclusions: We anticipate that industry sponsors will acknowledge such training, eliminating redundant training requests. We proposed metrics to be tracked that required further study. A separate task force was composed to define recommendations for metrics to be reported to NCATS.